PROBLEMATIKA PENDIDIKAN ISLAM DI INDONESIA - Siti Suwaibatul Aslamiyah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2013)
Education as an important factor in the process of development and progress of human life, a very dominant center of attention from all walks of society, especially those who have the authority to develop, so that a variety of methods are used to develop it. However, that did not run smoothly and seamlessly as there are a variety of obstacles and problems that become an obstacle smooth the business, especially at a time like now, in the midst of the complexity of the problems of the nation and the state.Therefore, in the article entitled